Diversity of Pollinator Insects in the Kebun Raya Institut Teknologi Sumatera - Maretta, Gres; Prastyo, Agung; Darmawan, Andy (Pusat HKI, Paten, dan Publikasi Ilmiah Universitas Islam Negeri Raden Intan Lampung, 2025)
Pollinator insects are insects that help the pollination process in plants by transferring pollen to other plants. The pollen attaches to the hairs and legs of the insect at the time when the pollinator's insect is foraging. This study aimed to analyze the diversity index and dominance index of pollinator insects in the Kebun Raya Institut Teknologi Sumatera. This research was conducted at the Kebun Raya Institut Teknologi Sumatera, specifically the orchard (guava and dragon fruit) and aesthetic garden. This study used purposive sampling by taking data directly at the observation site. Data analysis was used to calculate the diversity of pollinator insects within the ecosystem. The analysis involved calculating the diversity index (H') and dominance index (D). The study shows that pollinator insects come from 5 orders: Coleoptera, Diptera, Hemiptera, Hymenoptera, and Lepidoptera. Each observation location in the Kebun Raya Institut Teknologi Sumatera has a moderate category diversity index: guava orchards 1.93, dragon fruit orchards 1.53, and aesthetic gardens 1.60. The dominance index of each observation site showed values with low categories, namely guava orchards at 0.18, dragon fruit orchards at 0.32, and aesthetic gardens at 0.28. Visiting activities in the morning are dominated by the family Apidae, while daytime and afternoon are dominated by the family Nymphalidae. High temperatures lead to decreased activity of pollinator insects.